The joy in the thought of Clément Rosset - Viramontes Cabrera, Sonia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The tragic thought of Clément Rosset cannot be understood without one of its key concepts: joy. It is not an exaggeration tos ay that his philosophy could be summed up in the following sentence “le tus rejoice, because the worst in inevitable”, despite the fact that life is revealed to the autor as absurda n miserable, his philosophy finds in the joyo f living, the attitude more consistent with that way of seeing the world.